(untitled) (Damascus University Journal for engineering sciences, 2021)
Byzantine art is considered as the crucible in which various Greek, Roman, Aramaic and Persian art samples and elements were melted. Each had its own intellectual, philosophic and ideological privacy that formed the foundations of those elements. Nevertheless, we find that the Byzantine art was unique and original in form and substance. With the existence of Christianity and change in thought, especially under the Emperor Constantine, Byzantine art appeared with all its artistic elements as a result of the religious era in which Christianity triumphed. Art used to glorify state and god of Christianity. Such an art was a source of inspiration characterized by spiritual and mystical touch that reflected a deep and sublimated consciousness. Thus, art was embodied in various forms such as: painting (which included ornamentals, murals, frisks, and mosaic) and sculpture in spite of the Byzantine society fears of the existence of sculptures for different reasons: firstly, returning to idolatry, and secondly, the influence by the Greek belief that those statues were possessed by demonic spirits. Therefore, Sculpture occupied a special status, as it was not only a self-contained art, but it became a part of architecture or ornamentation of some ecclesiastical artistic elements.